Upgrading framed structure seismic performance using steel Lever-Armed dampers in the Braces. (1st April 2023) - Ellsa Sarassantika, I.P.; Hsu, H.-L.
Highlights: Performance enhancement inframed structures with novel LAD-Braceswas experimentally validated. Important experimental information was presented. Effective guidelines forLAD-Brace determinations in framed structures were proposed. Time-history responses of multi-story framed structures were adequately conducted and evaluated. Applicabilityof LAD-Braceinframed structural performance upgradingwas effectively validated. Abstract: This study evaluated the performance of frames equipped with novel lever-armed dampers in the braces (LAD-Brace). Cyclic loading tests and time-history response simulations using various earthquake ground motions were conducted on framed structures with and without LAD-Braces. The experimental results confirmed that the LAD-Braces effectively enhanced the strength of the structures. Significant achievements in elastic and inelastic stiffness of LAD-Braced frames over the SMRF justified the adequacy of the proposed design in deformation control and stability assurance. Simultaneous yielding on entire energy dissipation plate length incurred effective energy dissipation mechanism and efficient damping characteristics of the LAD-braced frames. LAD-Brace structural applicability was further evaluated by multi-bay-multi-story framed structural simulations using 11 different earthquake excitations. The simulation included the comparison of LAD-Braced frames to SMRFs and CBFs structure. The time-history structural responses revealed that the maximum story drifts and residual drifts of LAD-Braced frames were significantly reduced when compared with the corresponding SMRFs. In contrast to CBFs, analytical results showed that the LAD-Braced frame base shears were maintained at magnitudes equal to or less than the values of the corresponding SMRFs. This phenomenon combined with the effective reductions in story drifts and residual drifts validated the applicability of LAD-Brace in framed structural performance upgrading.